Competency Alignment and JOB Placement Analysis of Echelon Officials in Pasuruan Regency - Muhammad Tahajjudi Ghifary; Bambang Sutikno; Ascosenda Ika Rizqi (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
Effective bureaucratic management depends on aligning competencies with job placement. This study examines Echelon 3 and 4 officials in Pasuruan Regency, Indonesia, focusing on the suitability of their educational backgrounds, skills, and job roles. A descriptive quantitative approach was used with 77 respondents, including 23 Echelon 3 and 54 Echelon 4 officials. The findings indicate moderate suitability, with an average score of 3.5 out of 5. While many officials possess advanced educational qualifications, gaps in training adequacy and skill alignment remain. Technology usage is a key strength, reflecting readiness for digital transformation. These results emphasize the need for systematic training and strategic human resource allocation to enhance bureaucratic effectiveness. The study contributes to discussions on workforce optimization in public administration, providing actionable insights for policymakers. Future research should expand on these findings by exploring competency-based interventions and their impact on organizational performance.